Processing of polymer nanocomposites - Kenig, Shmuel (Munich Hanser Publications, 2019)
Covers the fundamental unit operations involved in processing of thermoplastic and thermoset nanocomposites. The processing methods include extrusion, injection molding, blow molding, and thermoforming. Also covered are nanoparticle dispersion, distribution, and compatibilization, and applications of polymer nanocomposites.